2013
DOI: 10.2196/jmir.2772
|View full text |Cite
|
Sign up to set email alerts
|

Online Mental Health Resources in Rural Australia: Clinician Perceptions of Acceptability

Abstract: BackgroundOnline mental health resources have been proposed as an innovative means of overcoming barriers to accessing rural mental health services. However, clinicians tend to express lower satisfaction with online mental health resources than do clients.ObjectiveTo understand rural clinicians’ attitudes towards the acceptability of online mental health resources as a treatment option in the rural context.MethodsIn-depth interviews were conducted with 21 rural clinicians (general practitioners, psychologists,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
97
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 37 publications
22
97
0
1
Order By: Relevance
“…Provider satisfaction: Based on 11 studies that use qualitative self-report methods, providers tend to have mixed reactions to telepsychiatry [25,33,34,[44][45][46][47][48][49][50][51][52] . Some studies have shown that adult and child psychiatrists reported adequate to high satisfaction with telepsychiatry [53] and one study demonstrated that mental health providers prefer telepsychiatry over telephone-based consultation [51] .…”
Section: Patient Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Provider satisfaction: Based on 11 studies that use qualitative self-report methods, providers tend to have mixed reactions to telepsychiatry [25,33,34,[44][45][46][47][48][49][50][51][52] . Some studies have shown that adult and child psychiatrists reported adequate to high satisfaction with telepsychiatry [53] and one study demonstrated that mental health providers prefer telepsychiatry over telephone-based consultation [51] .…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…Finally, some investigators have documented negative reactions to telepsychiatry as providers are resistant to use telepsychiatry [55] and concern that perceived technological challenges associated with telepsychiatry may hinder doctor-patient interactions [56] . Qualitative interviews yield similarly mixed results as some allied health providers report satisfaction with telepsychiatry services [44] , while others [45,46] express concerns about the potential adverse impacts of telepsychiatry on the therapeutic alliance and cited barriers …”
Section: Patient Satisfactionmentioning
confidence: 99%
“…In addition, stigmatized beliefs about mental illnesses have been identified as global problem for both help-seeking persons as well as for the diffusion of mental health services [4-6]. With respect to limited capacities of health care, the dissemination of Internet-delivered psychological services is suggested as an efficient strategy to improve the access to professional help by overcoming structural or regional barriers [2,3,7,8] and the stigma of seeking help for mental health problems [9,10]. Internet-delivered computerized, electronic mental health (e-mental health) services include the usage of modern digital technologies and new media in, for instance, monitoring, screening, psychoeducation, prevention, health promotion, self-help, counseling, aftercare, and psychotherapy [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies emphasize the importance of contextual factors of daily clinical practice, such as the level of knowledge and training, available time and resources, perceived social norms, forces within the current care system, and the design and usability of the technological tools [14,16,[19][20][21][22][23][24][25].…”
Section: Not Limited To Therapy Consultation and Psycho-education Bmentioning
confidence: 99%
“…[14,20,22]), whereas other studies took a more exploratory approach (e.g. [21,23,24,33,34]. However, this research has mainly resulted in lists of factors that impact the adoption of online treatment without structuring their relative weights or considering the influence of individual differences in practitioners' willingness and experience to explore and use online therapeutic tools.…”
Section: Not Limited To Therapy Consultation and Psycho-education Bmentioning
confidence: 99%